2016
DOI: 10.1139/cgj-2015-0194
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic considerations for the design of deep foundations against excessive differential settlement

Abstract: Current foundation design practice for serviceability limit states involves proportioning the foundation to achieve an acceptably small probability that the foundation settlement exceeds some target maximum total settlement. However, it is usually differential settlement that leads to problems in the supported structure. The design question, then, is how should the target maximum total settlement of an individual foundation be selected so that differential settlement is not excessive? Evidently, if the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Soil variability is a major issue in geotechnical engineering (Honjo, 2011); it typically causes uncertainty in the interpretation of site investigations and has important, but different, implications for different geotechnical structures. The influence of spatial variability has been studied, by way of the use of theoretical and numerical models, in relation to shallow, strip and pile foundations (Jaksa et al, 2005;Suchomel & Masín, 2010;Naghibi et al, 2016), retaining walls (Sert et al, 2016), liquefaction of hydraulic sand fills (Wong, 2004;Hicks & Onisiphorou, 2005;Popescu et al, 2005) and slope stability (Griffiths & Fenton, 1997;Hicks & Samy, 2002;Hicks & Spencer, 2010;Li et al, 2016). It has been shown, especially for embankments (Spencer & Hicks, 2007;Hicks & Spencer, 2010;Hicks et al, 2014;Hicks & Li, 2018), that the spatial variability of material properties, the problem geometry and the combination of the two are significant factors influencing the stability of slopes and the failure mode.…”
Section: Introductionmentioning
confidence: 99%
“…Soil variability is a major issue in geotechnical engineering (Honjo, 2011); it typically causes uncertainty in the interpretation of site investigations and has important, but different, implications for different geotechnical structures. The influence of spatial variability has been studied, by way of the use of theoretical and numerical models, in relation to shallow, strip and pile foundations (Jaksa et al, 2005;Suchomel & Masín, 2010;Naghibi et al, 2016), retaining walls (Sert et al, 2016), liquefaction of hydraulic sand fills (Wong, 2004;Hicks & Onisiphorou, 2005;Popescu et al, 2005) and slope stability (Griffiths & Fenton, 1997;Hicks & Samy, 2002;Hicks & Spencer, 2010;Li et al, 2016). It has been shown, especially for embankments (Spencer & Hicks, 2007;Hicks & Spencer, 2010;Hicks et al, 2014;Hicks & Li, 2018), that the spatial variability of material properties, the problem geometry and the combination of the two are significant factors influencing the stability of slopes and the failure mode.…”
Section: Introductionmentioning
confidence: 99%
“…For pile groups with caps of various thickness, the design concern becomes the differential settlements (∆). A recent study [7] investigated the differential settlements between two piles installed in spatially variable soils, and suggested that ∆ is largest when θ is approximately equal to the spacing (s) between the piles. In their study, the soil is elastic and the spatial variation of Young's modulus is isotropic (θ ln x = θ ln y = θ ln z ).…”
Section: Probabilistic Analyses Of Pile Groups With Rigid or Flexible...mentioning
confidence: 99%
“…The designs of large pile groups or piled rafts are often controlled by differential settlements, which may cause distortion or tilting of the structure. However, in previous studies of probabilistic analyses of piles and pile groups [e.g., 1,2,3,4,5,6,7], there have been limited discussions on the uncertainties associated with these aspects of piled foundation response, and their interrelationship with spatial variability of soil properties and influence of superstructure. This may be partly attributed to the complex interaction effects in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very popular in various engineering design fields. During several years, the continuous development of computer technology, people continue to develop a variety of finite element analysis software [16][17]. In solving the complex conditions of foundation pit engineering method, the application of numerical analysis software is also quite common.…”
Section: Introductionmentioning
confidence: 99%